In vitro and in vivo studies of Cucurbita pepo L. flowers: chemical profile and bioactivity. Issue 17 (19th August 2021) - Morittu, Valeria M.; Musco, Nadia; Mastellone, Vincenzo; Bonesi, Marco; Britti, Domenico; Infascelli, Federico; Loizzo, Monica R.; Tundis, Rosa; Sicari, Vincenzo; Tudisco, Raffaella; Lombardi, Pietro
Abstract: Edible flowers consumption has increased in recent years due to their rich content of healthy phytochemicals. The aim of this study was to analyse the chemical profile of Cucurbita pepo L. flowers, and to explore their antioxidant and hypoglycaemic properties. Moreover, in order to assess in vivo effects, biochemical analysis, Reactive Oxygen Metabolites (d-ROMs) and Biological Antioxidant Potential (BAP) tests were performed on mice serum. High Performance Liquid Chromatography-Diode Array Detection (HPLC-DAD) analyses revealed the presence of (+)-catechin, (−)-epicatechin, rutin, and syringic acid as main constituents. 2, 2′-Azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) and Ferric Reducing Antioxidant Power (FRAP) tests showed interesting results. The extract exhibited the strongest inhibitory effect on α-glucosidase (IC50 of 144.77 μg/mL). In vivo results confirmed the hypoglycaemic effects, also affecting lipid metabolism but did not revealed benefits on ROS production. These results may add some information supporting the use of C. pepo flowers as functional foods and/or nutraceuticals. Abstract : UF0001